Direct Anatomical Reconstruction of the Achilles Tendon and Its Application for Surgical Treatment of Acute Achilles Tendon Ruptures - Alessandro Pisano; Gaetano Caruso (Surgical Techniques Development)
Background/Objectives: Acute ruptures of the Achilles Tendon (AT) are common injuries in the active population, in particular among men aged 30 to 50. Full functional recovery after this kind of injury is long and challenging and nowadays there is no universal “gold standard” strategy when dealing with them. Methods: When it comes to surgical treatment, various techniques have been described: in case of a typical lesion at the midportion of the tendon (which is the most common type), the basic principle of surgical repair is the end-to-end suture of the tendon stumps. The AT (“calcaneal tendon” according to the International Anatomical Terminology) is the strongest tendon of the human body, it is the conjunct tendon of the two Gastrocnemii Muscles and the Soleus Muscle and has a well-recognizable twisted structure: the subtendon from the Medial Head of the Gastrocnemius attaches postero-laterally on the calcaneal tendon footprint, the subtendon from the Lateral Head of the Gastrocnemius attaches antero-laterally and the subtendon from the Soleus attaches medially, therefore creating a 90° twist of the tendon structure. Results: the twisted structure of the human AT is of central importance to its biomechanics, since it gives the tendon a higher resistance to deformation and concurs in supination of the subtalar joint during gait. Conclusions: given the abovementioned anatomical and biomechanical premises, we believe that the restoration of the subtendons anatomy can lead to a better functional recovery of the Triceps Surae—Achilles Tendon complex, therefore we recently decided to adopt for open surgical repair the Direct Anatomical Reconstruction of the Achilles Tendon, which we describe in the present article.